Retrospective Radiographic Evaluation of AugmentTM Bone Graft Fusion. Issue 4 (16th October 2019) - Shelton, Trevor J.; Sheih, Alvin K.; Chang, Eric; Steele, Amy E.; Giza, Eric; Kreulen, Christopher D.
Category: Ankle, Ankle Arthritis, Hindfoot, Midfoot/Forefoot Introduction/Purpose: Augment is the first Food and Drug Administration approved synthetic bone substitute specifically formulated for foot and ankle procedures and have shown results comparable to autograft. Initial studies on the use of Augment for fusion procedures of the foot and ankle are encouraging but there remains a lack of radiographic outcomes on its use. The purposes of this study were to report on the radiographic fusion rate of Augment and identify risk factors for nonunion in patients treated with Augment. Methods: After institutional review board approval, a retrospective study was performed of all patients ages 18-85 who underwent arthrodesis of the ankle, hindfoot, or midfoot and used Augment alone or in combination with autograft and/or allograft. Patients were excluded if they did not have regular radiographic follow-up. Each operative report was examined for procedure performed and location of the foot involved. Post-operative radiographs were reviewed to look at union rate following surgery. Patient charts were reviewed for age, gender, Body Mass Index (BMI), smoking history, and diabetes to examine potential risk factors for nonunion. Continuous variables were reported in means ± standard deviations and differences determined between those that fused and those that did not using a Wilcoxon Rank Sums test. Categorical variables reported as number of patients (percent of patients) and differences determined between those that fused and those that did not using a Fisher's exact test. Results: A total of 71 patients (average age at injury 57±14 years; 35 males (49%), 36 females (50%); BMI 31±6) underwent 33 (46%) midfoot arthrodesis, 41 (58%) hindfoot arthrodesis, and 27 (38%) ankle arthrodesis. A total of 58 patients (82%) went on to achieve fusion while 13 (18%) did not. There was no difference in gender (p=0.135), age (p=0.345) or BMI (p=0.196) between those who achieved fusion and those who did not. Patients with diabetes had a greater risk of nonunion compared to those who did not (p=0.033) while current smoking status or revision fusion did not pose a risk factor (p=1.000) (Table 1). There were no differences in part of the foot/ankle involved (p=0.445) or bone graft used (p=0.303). Conclusion: This the first study to examine the radiographic follow up of union using Augment. The most important finding of this study is that the rate of fusion in foot and ankle arthrodesis using Augment is near 82%. Diabetes is a risk factor for nonunion when using Augment. Smoking, gender, age, BMI, autograft vs allograft, and part of the foot or ankle fused did not pose a risk factor.